2009
DOI: 10.3109/15476910903258260
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabromobisphenol A has immunosuppressive effects on human natural killer cells

Abstract: Human natural killer (NK) cells are lymphocytes that destroy tumor cells, virally infected cells, and antibody-coated cells. Tetrabromobisphenol A (TBBPA) is used both as a reactive and an additive flame retardant in a variety of materials and appears to contaminate the environment. TBBPA has been found in human blood samples and if it interferes with NK cell function, this could increase risk of tumor development and/or viral infection. This study examines the effects of exposure to various concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…HBCD and TBPPA are used as flame retardants and significantly contaminate the environment, with detectable levels being found in human tissues (Covaci et al, 2006; Knutsen et al, 2008; Hagmar et al, 2000; Nagayama et al, 2001; Thomsen et al, 2002). Both compounds are able to decrease the lytic function and cell surface protein expression of human NK cells (Hinkson & Whalen, 2009; Hinkson & Whalen, 2010; Kibakaya et al, 2009; Hurd & Whalen, 2011). This inhibition of NK lytic function may be due to their ability to induce activation/phosphorylation of MAPKs and MAP2Ks (Cato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBCD and TBPPA are used as flame retardants and significantly contaminate the environment, with detectable levels being found in human tissues (Covaci et al, 2006; Knutsen et al, 2008; Hagmar et al, 2000; Nagayama et al, 2001; Thomsen et al, 2002). Both compounds are able to decrease the lytic function and cell surface protein expression of human NK cells (Hinkson & Whalen, 2009; Hinkson & Whalen, 2010; Kibakaya et al, 2009; Hurd & Whalen, 2011). This inhibition of NK lytic function may be due to their ability to induce activation/phosphorylation of MAPKs and MAP2Ks (Cato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TBBPA was able to compete with thyroid hormone, T4, for binding to human transthyretin (thyroid hormone transport protein) in vitro (Meerts et al, 2000). TBBPA, like HBCD, decreases the cytolytic function of human NK cells while decreasing cell surface proteins and activating p44/42 (Cato et al, 2014; Kibakaya et al, 2009)…”
Section: Introductionmentioning
confidence: 99%
“…TBBPA was an immunosuppressant in in vitro cell systems including suppression of NK cell activity (Hurd and Whalen, 2011; Kibakaya et al, 2009). Mice treated with TBBPA were less able to mount a defense against viral infection (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory have shown that human NK cells exposed to HBCD or TPBPA exhibit significantly decreased lytic function and cell surface protein expression (Hinkson and Whalen, 2009; Hinkson and Whalen, 2010; Kibakaya et al, 2009; Hurd and Whalen, 2011). In the current study, we examine the activation states of the MAPK pathway in NK cells.…”
Section: Introductionmentioning
confidence: 88%
“…There are limited studies on the toxicological effects of HBCD and TBBPA on humans (Hinkson and Whalen, 2009; Hinkson and Whalen, 2010; Kibakaya et al, 2009). However there have been studies on lab animals.…”
Section: Introductionmentioning
confidence: 99%